POSSIBILITIES OF ENDOVASCULAR INTERVENTIONS IN TREATMENT OF BUDD-CHIARI SYNDROME - S. A. Alent’Ev; B. N. Kotiv; S. Ya. Ivanusa; P. N. Zubarev; I. I. Dzidzava; D. P. Kashkin; A. L. Muzharovskiy (Вестник хирургии имени И.И. Грекова, 2015)
The article presents the results of endovascular treatment of 35 patients with Budd-Chiari syndrome. An analysis of efficacy of modern interventions was made. There were shown the possibilities of balloon dilatation of stenosis of renal veins, the balloon dilatation and stenting with metal self-expansible stents of stenosis an occlusion of intrahepatic section of the postcava and results of transhepatic portsystemic bypass surgery.